Pentahelix Model in Revenue Optimization of Restaurant, Hotel and Amusement Tax Through Tapping Box in Kolaka Regency - Firdaus Firdaus; Bustang Bustang (Publik : (Jurnal Ilmu Administrasi), 2021)
To avoid gaps in tax leakage, the Kolaka Regency Government made a policy in the form of Regent Regulation Number 24 of 2019 concerning Online-Based Payment and Collection of Regional Taxes and Levie. A few months since the installation of this tool, the amount of tax revenue is always increasing. Then the receipts fluctuated and were added again due to the covid-19 pandemic even though there had been an increase in the number of installations of tax recording devices. The purpose of this study is to explore the Pentahelix Model in optimizing online tax revenue. This research method uses qualitative methods and phenomenological research types. The results of this study indicate that the element in Pentahelix, namely the government as a policy maker, has not yet developed a Standard Operating Procedure (SOP) related to the management of tapping boxes. There are still business people who have not committed to inputting each of their business transactions. There are still people who refuse to input transaction data into the Tapping Box and have not taken the initiative to supervise business actors who are tax collectors who tend to be less cooperative with government policies. The media has not been maximal in providing information related to online tax collection policies and the phenomena that occur. The Pentahelix model which has five elements such as academics, government, business people, the community, and the media must synergize and collaborate with each other to exchange resources in order to increase the realization of online-based tax revenue in Kolaka Regency.